Pengaruh Praktik Green Bbanking, Human Capital Dan Penerapan Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di Bei (2019-2023) - Faustina Yuniarty Rebo; Hermi Hermi (Mathematics Education Study Program, 2025)
This research aims to analyze the influence of green banking, human capital and Corporate Social Responsibility (CSR) on the financial performance of Indonesian banking companies in 2019-2023. There are 47 banks registered on the IDX which will be the population for this research, however the sample size determined is a purposive sample so that the banks selected according to the sampling criteria are 102. The analysis method in this research is panel data analysis with the help of Eviews 12. For financial performance in this research, profitability (ROA) is used. Green banking will be measured by the Green Banking Disclosure Index (GBDI), human capital by the VAHU formula and CSR by calculating the CSR index coverage. After conducting research, the implementation of green banking turned out to have a negative influence on revenue growth, while the human capital and CSR variables had a positive influence on revenue growth in corporate banking for the 2019-2023 period.